Expediente e Nominata - REVER, Revista (REVER: Revista de Estudos da Religião, 2021)
Avaliadores desta edição: Anderson de Oliveira Lima (USP, São Paulo-SP); Anna Carletti (UNIPAMPA, Bagé-RS); Cecilia Guimarães Bastos (UERJ, Rio de Janeiro-RJ); Christian David Soares Bitencourt (autônomo); Frederico Pieper (UFJF, Juiz de Fora-MG); José Adriano Filho (FUV, Vitória-ES); José Luiz Moraes Franco (IFPA, Belém-PA); Karina Oliveira Bezerra (autônoma); Marcos Alan S. V. Ferreira (UFPB, João Pessoa-PB); Maria Lucia Abaurre Gnerre (UFPB, João Pessoa-PB); Marina Lopes (AJES, Juína-MT); Pedro Moura (autônomo); Rodrigo Oliveira dos Santos (PUC-SP, Sâo Paulo-SP); Timóteo Cavaco (UCP, Portugal); Tom-Eric Krijger (Un. Leiden, Países Baixos); Viviane Zarembski Braga (IFTO, Palmas-TO)